Sukralfat as a Therapy for Reducing Itching and Repairing the Skin Barrier: A Systematic Review - Alia, Vrenda; Widhiati, Suci; Oktavriana, Triasari; Lidjaja, Lifesia Natali; Noviani, Laura (Journal La Medihealtico, 2024)
Sucralate is an aluminum salt from sucrose octasulfate that is known for its anti-ulcer activity, mucosal protection, and anti-mucositis potential. Recently, sucralfat has been used topically for the healing of various epithelial wounds, including ulcers, inflammatory dermatitis, mucositis, and burns. This systematic review aimed to evaluate the effectiveness of sucralfat as a topical therapy in reducing itching (pruritus) and improving the skin barrier. The analysis method used is Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA). A literature search was conducted on studies from 2004 to 2024 using keywords such as "sucralfate", "pruritus", "dermatitis", and "skin barrier" on PubMed, ProQuest, Science Direct, and Scopus databases. Inclusion criteria include topic relevance, research design, human subjects, and United Kingdom-speaking studies. Of the 141 articles found, 7 articles met the inclusion criteria. These studies involved a total of 605 subjects from different countries and used clinical trial methods and randomized controlled trials. The results showed that topical sucralfat was effective in reducing itching and improving the skin barrier in various skin conditions such as diaper dermatitis, chronic ulcers, and postoperative wounds. Sukralfat shows great potential in wound healing and skin barrier repair through the mechanism of protective layer formation, increased expression of epidermal growth factors, and anti-inflammatory properties. This effect indirectly helps reduce pruritus which often occurs due to damage to the skin barrier. Topical succulthate is effective in reducing itching and repairing the skin barrier, making it a promising therapy for a variety of inflammatory and ulcerative skin conditions.